An Analysis of Classroom Management in Teaching Speaking Skill at UPTD SMP Negeri 5 Gunungsitoli - Priskila Destalenta Tafona'o; Adieli Laoli; Trisman Harefa; Yasminar Amaerita Telaumbanua (Journal Of Language Education and Development (JLed), 2025)
This research aims to analyze classroom management applied in the process of teaching speaking skills in English classes. Classroom management is an essential aspect that influences the effectiveness of learning, especially in speaking skills, which require active interaction between teachers and students. This study employs a qualitative approach using observation, interview, and documentation methods involving English teachers and students at UPTD SMP Negeri 5 Gunungsitoli. The focus of the analysis includes classroom management strategies used by teachers to create a conducive learning environment, time management techniques, the arrangement of student interactions, and the handling of disturbances during speaking lessons. The findings reveal that teachers use a combination of classroom management techniques such as grouping students for discussions, providing clear instructions, and giving positive reinforcement to motivate learners. However, challenges remain in controlling distractions and maintaining students’ focus during speaking activities. This research recommends the need for specific training for teachers in effective and adaptive classroom management strategies to ensure that the teaching of speaking skills runs more optimally and results in maximum learning outcomes. Keywords :Classroom Management, Teaching Speaking Skill, Teacher Strategies, Learning Process, UPTD SMP Negeri 5 Gunungsitoli.